Impact Of Health Awareness Intervention Among The Women Sweepers Working Under The Midnapore Municipality Of West Bengal, India (Bangladesh Journal of Medical Science, 2013)
Background: Women sweepers is the vulnerable segment of our community and suffering from different occupational health problems due to limited education, lack of knowledge on occupational health hazards. The present study aimed to assess the awareness level regarding occupational health and personal hygiene and to evaluate the effect of occupational health intervention among the women sweepers. Methods: The study adopted a pre-test and post-test design. A total of 52 women sweepers in the age group of 25 to 60 years were selected randomly from Midnapore Municipality of West Bengal, India. At first, a self-structured questionnaire was prepared on the aspects of general health, occupational health, personal hygiene, environmental health and nutritional aspects. After the pre-awareness assessment an intervention package was delivered covering said domains. Than post testing was done on the participants after the period of intervention. Results: Results demonstrated that there was a considerable increase in the awareness levels among the women sweepers with regard to knowledge of health problems, occupational health. The knowledge of participants regarding personal hygiene improved markedly after imparting the intervention. With regards to preventive approaches of diseases among the women has increased after the intervention. Overall health knowledge increased significantly post-awareness stage than pre-awareness stage (P